EFFECTS OF SOCIOECONOMIC CHARACTERISTICS ON ACCESSIBILITY TO CREDIT IN COOPERATIVE THRIFT AND CREDIT SOCIETIES IN ILORIN-SOUTH LOCAL GOVERNMENT AREA OF KWARA STATE, NIGERIA. (Journal of the Management Sciences, 2024)
In Nigeria today, majority of the organizations, financial institutions, establishment, parastatals, Educational Institutions of learning have some yardstick using before considering people for loan or employment to any service. As a result of this Cooperative organization has some cogent tools using as collateral securities before granting members loan by Loan Committee through the final decision of Cooperative management. Simple random sampling technique was used to select sixty (60) Cooperators. This study employs the use of descriptive analytical tool such as: frequency count, means scores, percentage, cumulative to investigate the factors considering before given loan to members of the cooperative society. The result of the findings revealed that the major accessibility factors, that are significant to the study are, Age, Male, married, ordinary member, Christianity, Two bedroom apartment, Education, Maximum credit limit, Surety, Loan Defaulters, Favoritism, Loan Committee report, Repayment Period, Credit facility. It indicates that the management Committee considers the report of the Loan Committee before granting members final approval for loan in the Cooperative Society. It shows that all these factors have positive significant accessibility of loan in the study area. The minor factors that are not significant to the study are female, Traditional Religion, Large scale unqualified members and Loan Form. In conclusion, the accessibility to credit facilities by members in the study area is very important to the study.
Keywords: Socioeconomic, accessibility, credit, cooperatives, Kwara State, Nigeria